Edukasi Anti Perundungan Untuk Meningkatkan Kesadaran Siswa SD Melalui Program KKN di Desa Bersujud - Shinta Febby Wardiyana; Victoria Anggi Setiawati; Wanda Prastika; Jumriyani; Nur Hasanah; Muhamad Faturrohman Fadillah; Diah Kusuma Ladimah Petri P; M. Al Farizi; Nur Aisyah Azarah; Nur Wahdah Warahmah (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) of Nahdlatul Ulama University of South Kalimantan was conducted in Bersujud Village, Simpang Empat District, Tanah Bumbu Regency. One of the main programs focused on anti-bullying education in elementary schools. This program aimed to increase students’ awareness of the negative impacts of bullying and to foster empathy and mutual respect among them. Provide education regarding understanding hat the meaning of bullying itself is. The quasi-qualitative method includes initial observation, coordination with the school, preparation of socialization materials, implementation of interactive presentation activities, and post-activity evaluation through questions and answers and student reflection. The results indicated a significant improvement in students’ understanding of bullying behavior and in their positive attitudes toward peers. The program was highly appreciated by the school for creating a more positive and conducive learning environment. Therefore, the anti-bullying campaign through the KKN program serves as an effective strategy to instill moral values and empathy from an early age.